The response of small boreal catchments to extreme weather event: Hurricane Larry - Kavi M. Heerah; Kailee G. Clarke; Heather E. Reader (PLoS ONE, 2026)
The boreal environment is high in dissolved organic carbon (DOC) and iron concentrations. This DOC is enriched in functional groups allowing it to bind strongly with iron and act as a significant source of iron to the coastal and marine environment. As climate change intensifies more extreme weather events will affect the northern hemisphere and boreal environment. These weather events can lead to massive fluxes of material but the impact it will have is currently unknown. Hurricane Larry made landfall on Newfoundland (NL) in 2021 providing an opportunity to investigate how the boreal environment will react to extreme weather events. We sampled three rivers before and after the hurricane to see how DOC and iron concentrations, and colour (a 350 ) were affected by the hurricane. Temperature and pH were found to decrease in a statistically significant manner following the storm with iron and a 350 having a significant increase, DOC despite increasing following the storm failed to meet the statistical significance threshold. The rivers chosen had a high abundance of natural landcover which buffered the catchment’s response from the hurricane. Pearson’s correlations were calculated between the landcover and the ∆ of the variables to access the resilience of the catchments to extreme weather events. Due to the small sample size Pearson’s corelations could not achieve statistical significance but the results still provide a novel look into the resilience of the northern boreal regions to extreme weather events. These preliminary results show that a high percentage of forest and peatlands buffered against increases in DOC and colour, with wetlands buffering an increase in iron concentrations. This study represents one of the first to observe boreal catchment responses to extreme weather events such as hurricanes and can serve as basis for more robust studies based in the boreal region.